Roles of Lipid Peroxidation-Derived Electrophiles in Pathogenesis of Colonic Inflammation and Colon Cancer - Lei, Lei; Zhang, Jianan; Decker, Eric A.; Zhang, Guodong (Frontiers in Cell and Developmental Biology, 2021)
Redox stress is a common feature of gut disorders such as colonic inflammation (inflammatory bowel disease or IBD) and colorectal cancer (CRC). This leads to increased colonic formation of lipid-derived electrophiles (LDEs), such as 4-hydroxynonenal (4-HNE), malondialdehyde (MDA), trans, trans-2,4-decadienal (tt-DDE), and epoxyketooctadecenoic acid (EKODE). Recent research by us and others support that treatment with LDEs increases the severity of colitis and exacerbates the development of colon tumorigenesis in vitro and in vivo, supporting a critical role of these compounds in the pathogenesis of IBD and CRC. In this review, we will discuss the effects and mechanisms of LDEs on development of IBD and CRC, and lifestyle factors which could potentially affect tissue levels of LDEs to regulate IBD and CRC development.